Price variability or rigidity in the food-retailing sector? : Theoretical analysis and evidence from German scanner data - Herrmann, Roland; Möser, Anke; Justus Liebig University Giessen (My University, 2003)
In many industrialized countries, the grocery-retailing sector exhibits a strong and increasing market concentration. Hence, it is important to understand retail pricing for many questions related to market power in the marketing chain and to agricultural and food policies. We analyze intertemporal pricing of grocery retailers in Germany with a large set of scanner data for processed foods. In theory, food prices could be rather variable, e.g. due to fluctuating commodity prices in a competitive world, or rather rigid, e.g. due to price adjustment costs. We elaborate that retail sales are crucial and raise food price variability at the points of sale. Despite this, prices are rather rigid and often do not change for many weeks. Moreover, pricing strategies for identical brands vary strongly across retailers. Retailers seem to have differential pricing strategies and, thus, market power. This casts substantial doubt on the assumption of a competitive price transmission in the marketing channel underlying most analyses in agricultural economics.
Keywords: Deutschland; Lebensmitteleinzelhandel; Preispolitik; Grocery retailing sector; pricing patterns; sales; price rigidity; scanner data; ddc:650